Fusion Oncogenes Are Associated With Increased Metastatic Capacity and Persistent Disease in Pediatric Thyroid Cancers. Issue 10 (1st April 2022) - Franco, Aime T.; Ricarte-Filho, Julio C.; Isaza, Amber; Jones, Zachary; Jain, Neil; Mostoufi-Moab, Sogol; Surrey, Lea; Laetsch, Theodore W.; Li, Marilyn M.; DeHart, Jessica Clague; Reichenberger, Erin; Taylor, Deanne; et al.
Abstract : PURPOSE: In 2014, data from a comprehensive multiplatform analysis of 496 adult papillary thyroid cancer samples reported by The Cancer Genome Atlas project suggested that reclassification of thyroid cancer into molecular subtypes, RAS -like and BRAF -like, better reflects clinical behavior than sole reliance on pathologic classification. The aim of this study was to categorize the common oncogenic variants in pediatric differentiated thyroid cancer (DTC) and investigate whether mutation subtype classification correlated with the risk of metastasis and response to initial therapy in pediatric DTC. METHODS: Somatic cancer gene panel analysis was completed on DTC from 131 pediatric patients. DTC were categorized into RAS -mutant ( H-K-NRAS ), BRAF -mutant ( BRAF p.V600E), and RET / NTRK fusion ( RET, NTRK1, and NTRK3 fusions) to determine differences between subtype classification in regard to pathologic data (American Joint Committee on Cancer TNM) as well as response to therapy 1 year after initial treatment had been completed. RESULTS: Mutation-based subtype categories were significant in most variables, including age at diagnosis, metastatic behavior, and the likelihood of remission at 1 year. Patients with RET / NTRK fusions were significantly more likely to have advanced lymph node and distant metastasis and less likely to achieve remission at 1 year than patients within RAS- or BRAF -mut subgroups. CONCLUSION: Our data support that genetic subtyping of pediatric DTC more accurately reflects clinical behavior than sole reliance on pathologic classification with patients with RET / NTRK fusions having worse outcomes than those with BRAF -mutant disease. Future trials should consider inclusion of molecular subtype into risk stratification. Abstract :